Cerrorchestia taboukeli sp. nov., a new terrestrial amphipod (Amphipoda, Talitridae) from Martinique Island - Piscart, Christoph; Ayati, Khaoula; Coulis, Mathieu (European Journal of Taxonomy, 2019)
During recent investigations on the terrestrial invertebrates of the tropical rainforest on Martinique Island (Pitons du Carbet), specimens of a new species of the terrestrial amphipod genus Cerrorchestia Lindeman, 1990, C. taboukeli sp. nov., were collected by means of different quantitative and non-quantitative methods (hand collection and Tullgren extraction) in the forest floor. The new species can be easily distinguished from the only other species of the genus, C. hyloraina Lindeman, 1990, by gnathopod 2 (carpus short, palm longer than wide), pereopod 4 dactylus with a denticulate patch, pereopod 5 basis ovate with a deep posterodistal lobe reaching the distal end of the ischium, pleopod 3 ramus with more than six articles. Cerrorchestia tabouleki sp. nov. is the first forest-hopper discovered in the Lesser Antilles, raising the question of island colonization by terrestrial amphipods. Ecological data and a key to terrestrial Talitridae of Central America and the Caribbean islands are provided.